High efficiency TALENs enable F0 functional analysis by targeted gene disruption in Xenopus laevis embryos - Suzuki, Ken-Ichi T.; Isoyama, Yukiko; Kashiwagi, Keiko; Sakuma, Tetsushi; Ochiai, Hiroshi; Sakamoto, Naoaki; Furuno, Nobuaki; Kashiwagi, Akihiko; Yamamoto, Takashi (Biology Open, 2013)
Summary Recently, gene editing with transcription activator-like effector nucleases (TALENs) has been used in the life sciences. TALENs can be easily customized to recognize a specific DNA sequence and efficiently introduce double-strand breaks at the targeted genomic locus. Subsequent non-homologous end-joining repair leads to targeted gene disruption by base insertion, deletion, or both. Here, to readily evaluate the efficacy of TALENs in Xenopus laevis embryos, we performed the targeted gene disruption of tyrosinase (tyr) and pax6 genes that are involved in pigmentation and eye formation, respectively. We constructed TALENs targeting tyr and pax6 and injected their mRNAs into fertilized eggs at the one-cell stage. Expectedly, introduction of tyr TALEN mRNA resulted in drastic loss of pigmentation with high efficiency. Similarly, for pax6, TALENs led to deformed eyes in the injected embryos. We confirmed mutations of the target alleles by restriction enzyme digestion and sequence analyses of genomic PCR products. Surprisingly, not only biallelic but also paralogous, gene disruption was observed. Our results demonstrate that targeted gene disruption by TALENs provides a method comparable to antisense morpholinos in analyzing gene function in Xenopus F0 embryos, but also applies beyond embryogenesis to any life stage.